Plantas indesejadas ou alimentos nutritivos? análise de aceitação e viabilidade do consumo de plantas alimentícias não convencionais (PANC’s) - Silva, Bárbara (2022)
Food plants are those that have one or more parts or products that can be used in food, such as: roots, tubers, bulbs, rhizomes, stalks, leaves, shoots, flowers, fruits and seeds or even latex, resin and gum, or that are used to obtain edible oils and fats. Many plants are called "weeds" or "weeds" because they grow among the cultivated plants; however, they are species with great ecological and economic importance. These plants, called PANC'S (Unconventional food plants), term first used by Kinupp & Lorenzi to describe this type of neglected plant, can be alternative sources of nutrients, especially vitamins and minerals. The objective of this investigation was to gather information in the literature about the Non-Conventional Food Plants and what potential exists in the caatinga, the biome of the Pernambuco Agreste, connecting the results found with the academic community's understanding of this vegetation and the level of acceptance of their consumption. The work was divided into three stages: a bibliographic survey in the digital platforms Scholar Google (Google Scholar) and SciELO, two exploratory exhibitions, and a form (Google Forms) with some questions. From the results obtained in the questionnaire, it is clear that there is widespread knowledge about PANCs, considering that of the 98 responses, the analyzed ones had an average above 50%.